Membrane bioreactor for mall wastewater treatment - Everton Luis Butzen (Revista Ambiente & Água, 2020)
Malls concentrate a large number of people in a relatively small area, and thus generate concentrated urban wastewater. This study evaluated the performance of a membrane bioreactor (MBR) as an alternative for the treatment of mall wastewater. Wastewater samples without any previous treatment were collected from a medium-size mall and showed a high chemical oxygen demand (COD) near 2,000 mg L-1. The MBR operated with a constant pressure of 40 kPa during 60 days with a sludge age of 30 days. Concentration of biomass was 3,738±930 mg L-1 and average permeate flux was 7.0 L h-1 m-2. The MBR was able to remove 91.2% and 97.2% of color and turbidity, respectively. Furthermore, COD removal was approximately 90% and biochemical oxygen demand (BOD) 88%. In addition, the MBR produced a phosphorus removal near 50%, and for nitrogen, 80%. The MBR system proved to be an efficient process for the removal of the pollutants, remaining stable even with the oscillation of the characteristics of the raw sewage, presenting great potential for application in the treatment of sewage from malls and effluents with high organic loads.